A Neglected Genealogy of the Martyred Heroines of Islam: (Re)-writing Women’s Participation in Jihad Into the History of Late Imperial Gansu - Previato, Tommaso (Journal of Muslim Minority Affairs, 2018)
As agents of religiously-sanctioned violence, Muslim female fighters have only recently started to attract academic attention. Relevant scholarship has so far exclusively focused on the Middle East and the traditional centers of Islam, while almost nothing has been written with regard to Chinese Islam, whose fighting heroines have gone widely unnoticed. The present study is a first tentative attempt to bridge this gap in scholarship and put forth an alternative model of Muslim femininity which takes into account the divergent roles of women as both victims and perpetrators of violence, as well as their invaluable contribution to the transmission of religious knowledge. By comparing the stories of Arab women who fought during the early conquests and those subsumed within the anti-state narrative of Sufi sectarians from China’s northwestern province of Gansu, the effort made by Jahri female practitioners in the uprisings of mid- and late-Qing times is hence (re)-written into the history of Muslim warfare.
Created from Fastlane, Scopus look-up
Keywords: female fighters; history of warfare; Muslim femininity; perpetrators; victims